Anti-inflammatory activities in Stachytarpheta jamaicensis (L.) vahl ethyl acetate leaf extract - Liew, Pearl Majorie (2017)
Objective: Inflammation is regarded as a complicated pathophysiology process that triggered by direct activation of receptors or by the secretion of inflammatory mediators. However, if prolonged, can lead to tissue damage as well as pathogenesis of fatal diseases. Inflammation is currently treated by nonsteroidal anti-inflammatory drugs (NSAIDs). Unfortunately, these drugs caused severe side effects, such as gastrointestinal bleeding and cardiovascular diseases. Stachytarpheta jamaicensis (L.) Vahl has been used traditionally as herbal remedy in the treatment of inflammatory diseases. Nevertheless, little is known on the anti-inflammatory benefits of this plant. Thus, this research work aimed to scientifically evaluate and validate the anti-inflammatory activities of an ethyl acetate extract of Stachytarpheta jamaicensis (L.) Vahl (EASJ) as agents for treating inflammatory complications, using in vitro and in vivo models of inflammation. This study was also designed to investigate the possible molecular mechanisms involved in this activity. Methodology: EASJ was prepared by overnight soaking of the oven-dried powdered leaves in ethyl acetate. The extract was then filtered and evaporated to dryness. This study was determined using two different inducers (lipopolysaccharides, LPS and hydrogen peroxide, H2O2) and two different cell lines (RAW 264.7 murine macrophages and human umbilical veins endothelial cells, HUVECs). The cytotoxicity of EASJ on both RAW 264.7 murine cells and HUVECs was evaluated by MTT assay. As in all the subsequent experiments, the cells were pre-treated with EASJ (10, 50 and 75 μg/mL) followed by stimulation with LPS or H2O2. The anti-inflammatory properties of EASJ were evaluated by measuring NO production, expression of soluble cell adhesion molecules (CAMs) and in vivo vascular permeability (Miles assay) induced by LPS. Additionally, the effect of EASJ on in vitro vascular permeability, actin cytoskeleton rearrangement, VE-cadherin expression, reactive oxygen species (ROS) production and cAMP signalling activity were also determined in H2O2- stimulated HUVECs. Results: EASJ was able to significantly reduce the excessive NO production. Collectively, FITC-dextran permeation in HUVECs as well as vessel leakage in the skin of mice, in response to the inflammatory factors LPS and H2O2, were reduced by EASJ treatment. In addition, pre-treatment with EASJ significantly inhibited actin stress fibers formation and VE-cadherin disruption on H2O2-challenged HUVECs. EASJ showed a significant reduction in inhibiting ROS level in a dose-dependent manner. However, EASJ did not inhibit the increased expression of soluble ICAM-1 and VCAM-1 in HUVECs triggered by LPS. Interestingly, EASJ was able to upregulate the concentrations of cAMP level. Conclusion: Based on these observed activities, it was showed that EASJ exhibited protective effects against LPS-induced inflammation and H2O2-induced oxidative stress. This activity was related to the upregulation of cAMP signaling activity. This mechanism contributed, at least in part, to the antiinflammatory actions showed by this plant.